A modified strength capacity for composite slab using reliability approach - Mohammed, Kachalla (2016)
Design shear resistance coupled with lack of a probabilistic framework for the al- ternate deection requirement check for reinforced concrete (RC) slab, and the un- economical approach for pro_led composite slab strength determination are main challenges that contribute to design conservatism. This thesis proposes to ad- dress these challenges by implementing a rational- based approach in developing schemes for limit state performance enhancement and a numerical function for pro_led composite slab strength devoid of experimental procedure. Performance enhancement schemes employs the probabilistic safety appraisal in providing im- provement measures to the concrete shear resistance function and the provision for a simpli_ed probabilistic deection check while maintaining an acceptable closed form solution. Hence, variable deection, _defl and shear resistance, _prop factors are introduced to modify the existing limit state. Similarly, a procedural algorithm lead to the development of pro_led composite slab strength determination function for both longitudinal shear estimation methods by considering section slenderness and deck characteristics. First, composite deck safety performance against the load ratio function leads to safety bounds de_nitions that takes into consideration section slenderness and sheeting deck characteristics values delineated through l=6 and l=8, culminating in the formation of modi_ed strength function. The proba- bilistic based optimisation scheme shows potentials to improve RC slab design by suggesting 4% design moment reduction. Similarly, the concrete shear capacity can be increased signi_cantly with an enhancement _prop factor of 2.0, and a similar _defl value of 5.15 is also proposed to shore up the limiting deection requirement check under the use of a concrete strength class of 30 MPa. Furthermore, the developed strength determination effectively performs well in mimicking the prob- abilistic deck performance and composite slab strength determination that shows improvement in strength load estimation difference between the two longitudinal shear methods to 12% from 26%. The strength test performance between the developed scheme and the experiment based test results indicates high similarity, demonstrating the viability of the proposed strength determination methodology developed in this study.